2016
DOI: 10.1002/cphc.201600289
|View full text |Cite
|
Sign up to set email alerts
|

Heavy‐Atom Labeled Transmembrane β‐Peptides: Synthesis, CD‐Spectroscopy, and X‐ray Diffraction Studies in Model Lipid Multilayer

Abstract: Transmembrane β-peptides are promising candidates for the design of well-controlled membrane anchors in lipid membranes. Here, we present the synthesis of transmembrane β-peptides with and without tryptophan anchors, as well as a novel iodine-labeled d-β(3) -amino acid. By using one or more of the heavy-atom labeled amino acids as markers, the orientation of the helical peptide was inferred based on the electron-density profile determined by X-ray reflectivity. The β-peptides were synthesized through manual Fm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 70 publications
(81 reference statements)
0
23
0
Order By: Relevance
“…Trp is known to serve as membrane anchor and orientates proteins in the lipid bilayer . Recently, it was demonstrated that this peptide motif is incorporated into a lipid bilayer preserving a well‐defined and conformationally stable 3 14 ‐helical structure . As was indicated by FRET experiments, this type of peptide has a low tendency to aggregate .…”
Section: Methodsmentioning
confidence: 90%
See 2 more Smart Citations
“…Trp is known to serve as membrane anchor and orientates proteins in the lipid bilayer . Recently, it was demonstrated that this peptide motif is incorporated into a lipid bilayer preserving a well‐defined and conformationally stable 3 14 ‐helical structure . As was indicated by FRET experiments, this type of peptide has a low tendency to aggregate .…”
Section: Methodsmentioning
confidence: 90%
“…According to the basic structural parameter of an ideal 3 14 ‐helix, which is three amino acids per turn with a pitch of 0.5 nm, the hydrophobic stretch of the peptides matches the hydrophobic thickness of POPC (2 D C ≈2.71 nm) and DOPC (2 D C ≈2.68 nm) . The CD spectra recorded in solution and lipid bilayer show the typical pattern of a right‐handed 3 14 ‐helix (Figure B, left and Figures S3 and S4 in the Supporting Information) with a minimum at 195 nm, a zero‐crossing at 202 nm and a maximum at 210 nm . A small shoulder around 225 nm results from absorption of the four hTrp .…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Neutron reflectivity contrast can be modified for the aqueous subphase 17 by changing the ra-tio of hydrogenated and deuterated water, while the amphiphile contrast can also be varied through deuteration. X-ray reflectivity (XRR) is sensitive to effective electron density, so amphiphiles can be labelled with heavy atoms to increase contrast 18 . More generally X-ray reflectivity can also be used to detect ion localisation at interfaces [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…In case of membrane insertion, the CD signal would have been shifted to shorter wavelengths. [22] In further experiments, the β-peptide membrane interaction will be supported by atomic force microscopy (AFM), which provides more information about the distance between β-peptides and the lipid bilayer.…”
mentioning
confidence: 99%